Observing The Judicial Commission’s Role In Enhancing Judicial Capacity And Integrity - Nurul Faizah Muhrim (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2021)
The purpose of this study is to examine the Judicial Commission's urgency in developing the capacity and integrity of judges in Makassar, as well as the mechanism for carrying out the Judicial Commission's duties in developing the capacity and integrity of judges from a siyasa syar'iyyah perspective. The research method used is descriptive qualitative field research. By adopting a syar'i normative perspective. The study's findings underscore the Judicial Commission's urgency in building the capacity and integrity of Makassar's judges through a training program on the Code of Ethics and Code of Conduct for Judges. The mechanism for carrying out the judicial commission's mandate of enhancing judges' capacity and integrity includes conducting training to improve KEPPH for judges with a tenure of 0–8 years, as well as the meaning of KEPPH for judges with a tenure of 8–15 years. In an Islamic state, the Judicial Commission serves as a supervisory agency for judges. It is headed by Qadhi al-Qudhat. This such, the Judicial Commission adheres to Islam's principle of being a supervisory entity in order to promote good behaviors and avert evil ones. The implication of this research is to strengthen the capacity and integrity of judges through the Judicial Commission's frequent implementation of judge training programs. Keywords: Judicial Commission; Judges; Siyasah Syar’iyyah